Implementation Of Internal Model Control (IMC) In Continuous Distillation Column. - Muhammad, D.; Ahmad, Z.; Aziz, N. (2010)
Distillation columns have been widely used in chemical plants for separation process. The high nonlinearity and dynamic behavior of the column make them hard to control.